Some Observations on the Life History and Behaviour of Digger Wasp Ammophila frythrocephala Fabricius (Sphecidae : Hymenoptera) - Misra, Ram Mohan (Indian Forester, 1984)
The dagger wasps are stinging predators. Life-history, field observation and territorial behaviour of Ammophila erythoephala were studied in Tira plantalions, Siwalik Forest Division. The egg is white, semitransparent. Incubation period is 3 days. Carval period is 5-6 days, pupal Period is 18 days. Stinging, dragging, storing and nest building habits of the digger wasp were observed. Sphecid serve mankind by killing countless number of lepidopteraus, larvae aod thus helps to keep the pest in check during epidemies.